Keberadaan Material Bambu sebagai Subtitusi Material Kayu pada Penerapan Desain Interior dan Arsitektur - Hartanti, Grace (Humaniora, 2010)
Wood is a building material that is frequently used as the main component in interior design and architecture. But, the use of wood is declining today and it is replaced by bamboo. Now, wood material is difficult to find and this condition causes high price in market. Article presents the availability of bamboo that has been known by our society because of its benefit. They use bamboo to meet their everyday life, such as clothes, food, and house needs. Bamboo is also used for the development of interior design as well as architecture , especially in Indonesia.